Perovskite precursor solution, solar cell, photovoltaic module and photovoltaic system

By adding self-assembled single-layer material to the perovskite precursor solution to construct an inorganic/organic composite structure, the problems of NiOx surface defects and insufficient conductivity are solved, and the performance and stability of perovskite solar cells are improved.

CN119816083APending Publication Date: 2025-04-11BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411625490.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In perovskite solar cells, nickel oxide (NiOx) is a hole transport layer material, and is limited by its surface defects and poor conductivity, resulting in the battery performance being unable to compare with that of batteries with traditional organic hole transport materials.

Method used

Self-assembled single-layer materials (SAMs) are added to the perovskite precursor solution, and an inorganic/organic composite structure is constructed on the NiOx surface to achieve in situ passivation of NiOx surface defects, and to improve the interface contact and energy level arrangement between the hole transport layer/perovskite absorbing layer.

Benefits of technology

Without increasing process complexity, the performance of solar cells is improved, combining the excellent performance of inorganic hole transport layer devices and organic hole transport layer devices, improving thermal stability and voltage efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005134718570000151
    Figure BDA0005134718570000151
  • Figure HDA0005134718710000011
    Figure HDA0005134718710000011
  • Figure HDA0005134718710000012
    Figure HDA0005134718710000012
Patent Text Reader

Abstract

The invention discloses a perovskite precursor solution, a solar cell, a photovoltaic module and a photovoltaic system. The perovskite precursor solution comprises a perovskite precursor and a self-assembled monomolecular layer material. The perovskite precursor solution is added with a self-assembly monomolecular layer material, in-situ passivation of NiOx surface defects can be realized, interface contact and energy level arrangement between a hole transport layer and a perovskite light absorption layer are improved, and the performance of a solar cell is improved on the premise that the process complexity is not increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a perovskite precursor solution, a solar cell, a photovoltaic module and a photovoltaic system. Background Art

[0002] As the third generation of new concept thin-film solar cells, perovskite solar cells have attracted much attention in the photovoltaic cost revolution due to their high efficiency, low cost, low energy consumption, and rich application scenarios. In perovskite solar cells, hole transport layer materials mainly include three types: organic polymer hole transport layer materials, inorganic P-type semiconductors, and small molecule self-assembly materials. Organic polymer hole transport layers usually have the characteristics of low deposition temperature and low temperature processing, but they may have complex synthesis processes and high costs. Self-assembled monolayer materials (SAMs), they provide efficient carrier transport, however, the essence of SAMs transport materials is monolayer adsorption, which may have problems such as tunneling, voids, and thermal instability.

[0003] Nickel Oxide (NiO x ) because it is easy to fill the gaps in the crystal lattice 2- To form Ni 2+ Vacancies are the representative of metal oxide P-type semiconductors and are often used as hole transport layer materials for perovskite solar cells. They have excellent thermal stability and cost advantages, but are limited by their high surface defects and poor conductivity. x The battery performance is still not comparable to that of batteries based on traditional organic hole transport materials. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to provide a perovskite precursor solution, a solar cell, a photovoltaic module and a photovoltaic system. The perovskite precursor solution of the present application is added with a self-assembled monolayer material to achieve NiO x In-situ passivation of surface defects improves the interface contact and energy level arrangement between the hole transport layer / perovskite light absorbing layer, thereby improving the performance of solar cells without increasing the complexity of the process.

[0005] The first aspect of the present application provides a perovskite precursor solution, wherein the perovskite precursor solution comprises: a perovskite precursor and a self-assembled monolayer material.

[0006] According to the embodiment of the present application, the perovskite precursor solution contains a self-assembled monolayer material, and the perovskite precursor solution is deposited on NiO x The self-assembled monolayer material does not participate in the perovskite phase formation, so it is squeezed into the NiO during the perovskite crystallization process. x / perovskite interface, thus at the NiOx Construct an inorganic / organic composite structure on NiO x In-situ passivation of surface defects improves the interface contact and energy level arrangement between the hole transport layer / perovskite light absorbing layer, thereby improving the performance of solar cells without increasing the complexity of the process.

[0007] According to an embodiment of the present application, the self-assembled monolayer material includes at least one of MeO-2PACz, MPA-CPA, DMACPA, 2PACz, Me-4PACz, Br-4PACz, Br-2PACz, TBT-FBA, 4PADCB, and 2PADCB;

[0008] And / or, the structural formula of the perovskite precursor is ABX3, wherein A includes at least one of methylamine ion, formamidine ion, acetamidine ion, cesium ion and rubidium ion; B includes at least one of lead ion, tin ion, copper ion and germanium ion; X includes at least one of fluoride ion, chloride ion, bromide ion, iodide ion, cyanide ion and thiocyanate ion.

[0009] According to an embodiment of the present application, the concentration of the self-assembled monolayer material is 0.1 mg / mL to 10 mg / mL.

[0010] In a second aspect, the present application provides a solar cell, comprising a perovskite light-absorbing layer, wherein the perovskite light-absorbing layer is formed by at least the perovskite precursor solution described in the first aspect.

[0011] According to an embodiment of the present application, a hole transport layer, a transparent conductive layer and a substrate are sequentially stacked on one side of the perovskite light absorbing layer, and an electron transport layer is stacked on a side of the perovskite light absorbing layer away from the hole transport layer.

[0012] According to an embodiment of the present application, the hole transport layer includes NiO x .

[0013] According to an embodiment of the present application, in the perovskite light absorbing layer, a concentration of the self-assembled monolayer material on a side close to the hole transport layer is higher than a concentration of the self-assembled monolayer material on a side away from the hole transport layer.

[0014] According to an embodiment of the present application, the self-assembled monolayer material accounts for 0.5‰ to 8‰ of the mass of the perovskite light-absorbing layer.

[0015] According to an embodiment of the present application, an electrode layer is stacked on a side of the electron transport layer away from the perovskite light absorbing layer.

[0016] According to an embodiment of the present application, an interface barrier layer is stacked between the electron transport layer and the electrode layer, and the interface barrier layer includes at least one of TiO2, ZnO, SnO2, and BCP.

[0017] The third aspect of the present application provides a method for preparing the solar cell according to the second aspect, the method comprising:

[0018] forming the hole transport layer on a side of the transparent conductive layer stacked on one side of the substrate and away from the substrate;

[0019] Applying the perovskite precursor solution of the first aspect to the side of the hole transport layer away from the transparent conductive layer, and annealing to form the perovskite light absorbing layer;

[0020] The electron transport layer is formed on a side of the perovskite light absorbing layer away from the hole transport layer.

[0021] According to an embodiment of the present application, after applying the perovskite precursor solution to the side of the hole transport layer away from the transparent conductive layer, vacuum assisted crystallization is performed, and then the annealing is performed.

[0022] According to an embodiment of the present application, a method of forming the hole transport layer includes at least one of spin coating, solution deposition and magnetron sputtering.

[0023] According to an embodiment of the present application, the vacuum assisted crystallization satisfies at least one of the following conditions:

[0024] Vacuum degree is 10Pa~0.2MPa;

[0025] Vacuum time is 1min~20min;

[0026] The vacuum rate is 0.1L / s~10L / s.

[0027] According to an embodiment of the present application, the method of applying the perovskite precursor solution includes at least one of blade coating, slit coating, spray coating, and evaporation;

[0028] And / or, the annealing temperature is 140° C. to 160° C., and the annealing time is 5 min to 20 min.

[0029] A fourth aspect of the present application provides a photovoltaic component, the photovoltaic component comprising: at least one battery string, the battery string comprising at least two solar cells according to the second aspect.

[0030] A fifth aspect of the present application provides a photovoltaic system, which includes: the photovoltaic component described in the third aspect.

[0031] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0033] Figure 1 A schematic diagram of the solar cell structure of an embodiment of the present application is shown;

[0034] Figure 2 A schematic diagram of a process for preparing a solar cell according to an embodiment of the present application is shown;

[0035] Figure 3 The 100×100 mm 2 Optical photograph of a perovskite film of size 1.447 mm / s.

[0036] Reference numerals:

[0037] 10: solar cell; 100: substrate; 200: transparent conductive layer; 300: hole transport layer; 400: perovskite light absorption layer; 500: electron transport layer; 600: electrode layer; 700: interface barrier layer. DETAILED DESCRIPTION

[0038] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0039] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.

[0040] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this application.

[0041] In the present application, the terms "comprise" or "include" are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0042] In perovskite cells, hole transport layer materials mainly include three categories: organic polymer hole transport layer materials, inorganic P-type semiconductors, and small molecule self-assembled materials (SAMs). Organic polymer hole transport layers usually have the characteristics of low deposition temperature and low temperature processing, but they may have complex synthesis processes and high costs. SAMs provide efficient carrier transport, however, the essence of SAMs is monolayer adsorption, and there may be problems such as tunneling, voids, and thermal instability. Inorganic P-type semiconductor transport layers usually exhibit good chemical stability and thermal stability. These advantages are of great significance to the development of long-life, low-cost large-area perovskite solar cell modules and their industrialization. Nickel oxide (NiO x ) because it is easy to fill the gaps in the crystal lattice 2- To form Ni 2+ Vacancy is a representative of metal oxide P-type semiconductors, and its work function can be changed by changing O 2- or Ni 2+ The concentration of NiO can be adjusted between 4.5 and 5.6 eV to achieve a good match with the energy level structure of the perovskite material. x The higher conduction band energy level (1.8 eV) can also effectively block the leakage of electrons from the perovskite material to the positive electrode, thereby showing better selectivity and better hole separation effect.

[0043] NiO x As a promising hole transport layer material for perovskite solar cells, it can be prepared by in-situ preparation, magnetron sputtering and NiO x It is processed and prepared by various methods such as nanoparticle deposition, which has excellent thermal stability and cost advantages, but is limited by its high surface defects and poor conductivity. x The battery performance is still not comparable to that of batteries based on traditional organic hole transport materials.

[0044] Traditional NiO x The optimization of the transport layer is mainly carried out through doping and interface modification. Doping with metal ions with good conductivity can improve the NiO x Conductivity of thin films, e.g. NiO before and after copper doping x The conductivity of the film can be increased by two orders of magnitude, reaching 10 -4 S / cm. In addition, copper-doped NiO (Cu:NiO x ) can improve the injection and transmission efficiency of holes, which is beneficial to improve the short-circuit current density and fill factor of the device. Other metal elements such as Cs, Li, Mg, Au and K are also doped into NiO x However, the above ion-doped NiO xWhile improving the conductivity, the method is accompanied by the formation of defects, resulting in a decrease in carrier mobility and carrier recombination, affecting the performance of photovoltaic devices. Interface modification is usually done on NiO x Depositing a separate modification layer on the HTL to achieve the solar cell performance of an organic HTL material increases the complexity of the process and may reduce repeatability during the process.

[0045] In view of this, the first aspect of the present application proposes a perovskite precursor solution, wherein the perovskite precursor solution comprises: a perovskite precursor and a self-assembled monolayer material.

[0046] According to the embodiment of the present application, the perovskite precursor solution contains self-assembled monolayer materials (SAMs). SAMs do not participate in the perovskite phase formation, so they are squeezed into the NiO during the perovskite crystallization process. x / perovskite interface, thus at the NiO x SAMs have strong orientation, and their hydrophilic groups and NiO x There is a strong force, deposited on NiO x After being added, it binds to NiO through strong PO···Ni or P=O···Ni bonds. x The bonding between the surface hydroxyl groups achieves the passivation effect. Therefore, without the additional deposition of hole transport layer and modification layer, NiO x In-situ passivation of surface defects improves the interface contact and energy level arrangement between the hole transport layer / perovskite light absorbing layer, thereby improving the performance of solar cells without increasing the complexity of the process.

[0047] Specifically, the solar cells made from the perovskite precursor solution have the excellent performance of both inorganic hole transport layer devices and organic hole transport layer devices. On the one hand, the perovskite device based on the inorganic hole transport layer material has better thermal stability and operating life under continuous sunlight. On the other hand, NiO x The energy alignment and good contact between / SAMs and perovskite are combined to reduce the voltage loss of perovskite solar cells.

[0048] In addition, the perovskite precursor solution is x The layer has good wettability, but the interface modification (i.e., on the NiO x The formation of a SAMs passivation layer on the perovskite surface often destroys this good contact interface and affects the coating uniformity of the perovskite. In this application, SAMs are used as additives and directly added to the perovskite solution to avoid the deposition of an additional passivation layer. The perovskite light absorption layer and NiO xIt can make good contact and improve the uniformity of large-area processing and preparation of perovskite film. In the embodiment of the present application, the SAMs hole transport material can be a SAMs hole transport material known in the art and suitable for perovskite cells. Specifically, the SAMs hole transport material includes but is not limited to (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid (MeO-2PACz), 4-(2,7-dibromo-9,9-dimethylacridine-10(9H)-yl)butyl)phosphonic acid (DMACPA), MPA-CPA (CAS No. 2212003-31-9), (2-(9H-carbazole-9-yl)ethyl)phosphonic acid (2PACz), (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl) Phosphonic acid (Me-4PACz), (4-(3,6-dibromo-9H-carbazole-9-yl)butyl)phosphonic acid (Br-4PACz), (2-(3,6-dibromo-9H-carbazole-9-yl)ethyl)phosphonic acid (Br-2PACz), triphenylphosphinothioic acid 2-fluorobenzoic acid (TBT-FBA), (4-(7H-dibenzo[c,g]carbazole-7-yl)butylphosphonic acid (4PADCB) and (4-(7H)-dibenzocarbazole-7-yl)ethyl)phosphonic acid (2PADCB).

[0049] According to an embodiment of the present application, the structural formula of the perovskite precursor is ABX3, wherein A includes at least one of methylamine ion, formamidine ion, acetamidine ion, cesium ion and rubidium ion; B includes at least one of lead ion, tin ion, copper ion and germanium ion; X includes at least one of fluoride ion, chloride ion, bromide ion, iodide ion, cyanide ion and thiocyanate ion.

[0050] According to an embodiment of the present application, the concentration of the self-assembled monolayer material is 0.1 mg / mL to 10 mg / mL, for example, 0.1 mg / mL, 0.2 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 0.8 mg / mL, 1 mg / mL, 2 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 8 mg / mL, 10 mg / mL, based on the total volume of the perovskite precursor solution. The concentration of the self-assembled monolayer material meets the above conditions, which can promote the formation of good crystallinity of perovskite crystals, enhance their uniformity, and optimize the surface morphology of the film, which helps to improve the energy conversion efficiency of perovskite solar cells and ensure their long-term operation stability.

[0051] In some embodiments, the perovskite precursor solution further includes a solvent, and the solvent includes at least one of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), 2-Mercaptoethanol (2-ME) and N-methylpyrrolidone (NMP).

[0052] The second aspect of the present application provides a solar cell. According to an embodiment of the present application, see Figure 1 The solar cell 10 includes a perovskite light absorbing layer 400, and the perovskite light absorbing layer is formed by at least the perovskite precursor solution described in the first aspect.

[0053] The self-assembled monolayer material (SAMs) in the perovskite light absorbing layer 400 does not participate in the perovskite phase formation and is therefore squeezed into the NiO during the perovskite crystallization process. x / perovskite interface, thus at the NiO x SAMs have strong orientation, and their hydrophilic groups and NiO x There is a strong force, deposited on NiO x After being added, it binds to NiO through strong PO···Ni or P=O···Ni bonds. x Therefore, without the need for additional deposition of hole transport layers and modification layers, NiO x In-situ passivation of surface defects improves the interface contact and energy level arrangement between the hole transport layer / perovskite light absorbing layer, and improves the performance of solar cells without increasing the complexity of the process. Solar cells combine the excellent performance of inorganic hole transport layer devices and organic hole transport layer devices. On the one hand, perovskite devices based on inorganic hole transport layer materials have better thermal stability and operating life under continuous sunlight. On the other hand, NiO x The energy alignment and good contact between / SAMs and perovskite reduce the voltage loss of perovskite solar cells. In addition, it avoids the x Additional passivation layers are deposited on the perovskite light absorbing layer with NiO x It can provide good contact and improve the uniformity of large-area processing and preparation of perovskite films.

[0054] According to an embodiment of the present application, a hole transport layer 300, a transparent conductive layer 200 and a substrate 100 are sequentially stacked on one side of the perovskite light absorbing layer 400, and an electron transport layer 500 is stacked on a side of the perovskite light absorbing layer away from the hole transport layer.

[0055] According to an embodiment of the present application, the hole transport layer includes NiO x .

[0056] According to an embodiment of the present application, in the perovskite light absorption layer 400, the concentration of the self-assembled monolayer material on the side close to the hole transport layer 300 is higher than the concentration of the self-assembled monolayer material on the side away from the hole transport layer 300. SAMs do not participate in the perovskite phase formation, so they are squeezed into the NiO during the perovskite crystallization process.x / perovskite interface, regional P-type doping is carried out to construct an inorganic / organic composite structure on NiOx.

[0057] According to an embodiment of the present application, the self-assembled monolayer material accounts for 0.5‰ to 8‰ of the mass of the perovskite light-absorbing layer, for example, it can be 0.5‰, 0.8‰, 1‰, 2‰, 3‰, 4‰, 5‰, 6‰, 7‰, 8‰. The content of the self-assembled monolayer material meets the above conditions, and the uniformity and surface morphology of the perovskite film are good, which helps to improve the energy conversion efficiency of the perovskite solar cell and ensure its long-term operation stability.

[0058] According to an embodiment of the present application, an electrode layer 600 is stacked on a side of the electron transport layer 500 away from the perovskite light absorbing layer 400. Exemplarily, the electrode layer includes one or more of gold, silver, copper and aluminum.

[0059] According to an embodiment of the present application, an interface barrier layer 700 is stacked between the electron transport layer 500 and the electrode layer 600, and the interface barrier layer 700 includes at least one of TiO2, ZnO, SnO2, and BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline). Thus, the energy level matching between the electrode and the electron transport layer is improved, the energy level barrier of electron injection is reduced, and the smooth transmission of electrons is promoted, which also helps to improve the long-term stability of the battery.

[0060] According to an embodiment of the present application, the substrate includes transparent glass.

[0061] According to an embodiment of the present application, the transparent conductive layer includes at least one of FTO, ITO, IZO, and AZO.

[0062] According to an embodiment of the present application, the electron transport layer includes: fullerene and its derivatives, cyanide-containing polyphenylene vinylene, boron-containing polymer, 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline, 4,7-diphenyl-1,10-phenanthroline, hydroxyquinoline aluminum, oxadiazole compounds, benzimidazole compounds, naphthalenetetracarboxylic acid compounds, perylene derivatives, phosphine oxide compounds, phosphine sulfide compounds, fluorinated phthalocyanine, titanium oxide, zinc oxide, indium oxide, tin oxide, gallium oxide, tin sulfide, indium sulfide, lithium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride and zinc sulfide. One or more.

[0063] According to the embodiments of the present application, in some embodiments of the present application, the hole transport layer includes: [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, benzoic acid, 4-[bis(2,4-dimethoxybiphenyl-4-yl)amino]biphenyl-4-carboxylic acid, [4-(7H-dibenzocarbazole-7-yl)butyl]phosphonic acid, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline, 2,2",7,7"-tetrakis[N,N-di(4 -methoxyphenyl)amino]-9,9'-spirobifluorene, [bis(4-phenyl)(2,4,6-trimethylphenyl)amine], poly(3-hexylthiophene-2,5-diyl), poly(3,4-ethylenedioxythiophene): poly(4-styrenesulfonic acid), 2,2',7,7'-tetrakis(N,N-di-p-tolyl)amino-9,9'-spirobifluorene, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanodimethyl-p-benzoquinone, hexafluoro-2,3,5,6-tetracyano-4-benzothiazoline, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], NiOx, CuSCN, CuAlO2, V2O5, CdS and CdSe. One or more.

[0064] It should be noted that the features and advantages described above for the first aspect are also applicable to the solar cell and will not be described in detail here.

[0065] The third aspect of the present application provides a method for preparing the solar cell described in the second aspect. According to the embodiments of the present application, see Figure 2 The method includes: forming a hole transport layer in step S100, forming a perovskite light absorption layer in step S200, and forming an electron transport layer in step S300. Each step will be described in detail below.

[0066] S100 forms a hole transport layer

[0067] In this step, a hole transport layer is formed on a side of the transparent conductive layer stacked on one side of the substrate and away from the substrate.

[0068] The present application does not impose strict restrictions on the method for forming the hole transport layer, which may include spin coating, solution deposition, magnetron sputtering, etc., and can be flexibly selected according to actual conditions.

[0069] S200 forms a perovskite light-absorbing layer

[0070] In this step, the perovskite precursor solution of the first aspect is applied to the side of the hole transport layer away from the transparent conductive layer, and annealed to form a perovskite light absorption layer. SAMs do not participate in the perovskite phase formation, so they are squeezed into the NiO during the perovskite crystallization process. x / perovskite interface, thus at the NiO x SAMs have strong orientation, and their hydrophilic groups and NiO x Therefore, without the additional deposition of hole transport layer and modification layer, NiO x In-situ passivation of surface defects improves the interface contact and energy level arrangement between the hole transport layer / perovskite light absorbing layer, thereby improving the performance of solar cells without increasing the complexity of the process.

[0071] According to an embodiment of the present application, after applying the perovskite precursor solution to the side of the hole transport layer away from the transparent conductive layer, vacuum assisted crystallization is performed, and then the annealing is performed. Thus, by reducing the ambient pressure, the solvent is caused to evaporate, thereby achieving rapid crystallization of the perovskite precursor solution without an external heat source.

[0072] According to an embodiment of the present application, the vacuum assisted crystallization satisfies at least one of the following conditions:

[0073] The vacuum degree is 10Pa to 0.1MPa, for example, 10Pa, 10 2 Pa, 10 3 Pa, 10 4 Pa, 10 5 Pa, 0.2Mpa;

[0074] The vacuum time is 1 min to 20 min, for example, 1 min, 2 min, 4 min, 5 min, 6 min, 8 min, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min;

[0075] The vacuuming rate is 0.1 L / s to 10 L / s, for example, it can be 0.1 L / s, 1 L / s, 2 L / s, 4 L / s, 6 L / s, 8 L / s, and 10 L / s.

[0076] The vacuum-assisted crystallization conditions meet the above conditions and can effectively promote the uniform nucleation and crystal growth of the perovskite precursor solution, thereby obtaining high-quality, uniform and dense perovskite films.

[0077] According to an embodiment of the present application, the method of applying the perovskite precursor solution includes at least one of blade coating, slit coating, spray coating and evaporation.

[0078] According to an embodiment of the present application, the annealing temperature is 140°C to 160°C, for example, 140°C, 145°C, 150°C, 155°C, 160°C; the annealing time is 5min to 20min, for example, 5min, 8min, 10min, 12min, 15min, 18min, 20min. Thus, the uniform nucleation and growth of perovskite crystals can be promoted, thereby improving the crystallization quality of the film.

[0079] According to an embodiment of the present application, the method further includes: sequentially forming an interface barrier layer and an electrode layer on a side of the electron transport layer away from the perovskite light absorbing layer.

[0080] It should be noted that the features and advantages described above for the solar cell are also applicable to the method for preparing the solar cell, and will not be described in detail here.

[0081] In the fourth aspect of the present application, the present application proposes a photovoltaic module, comprising at least one battery string, wherein the battery string comprises at least two solar cells described in the second aspect of the present application, or a solar cell prepared by the method for preparing a solar cell described in the third aspect of the present application. Therefore, the photovoltaic module has all the features and advantages of the aforementioned solar cell, which will not be described in detail here.

[0082] In some embodiments, the solar cells may be connected together by serial welding, so that the electric energy generated by the individual solar cells can be collected for subsequent transmission.

[0083] In some embodiments, the solar cells may be arranged at intervals or stacked together in a shingled form.

[0084] For example, the photovoltaic module further includes an encapsulation layer and a cover plate, wherein the encapsulation layer is used to cover the surface of the battery string, and the cover plate is used to cover the surface of the encapsulation layer away from the battery string.

[0085] In the fifth aspect of the present application, the present application proposes a photovoltaic system, including the photovoltaic assembly described in the fourth aspect of the present application. Therefore, the photovoltaic system has all the features and advantages of the aforementioned photovoltaic assembly, which will not be described in detail here.

[0086] Photovoltaic systems can be used in photovoltaic power stations, such as ground power stations, rooftop power stations, water power stations, etc., and can also be used in equipment or devices that use solar energy to generate electricity, such as user solar power supplies, solar street lights, solar cars, solar buildings, etc. Of course, it is understandable that the application scenarios of photovoltaic systems are not limited to this, that is to say, photovoltaic systems can be used in all fields that require solar energy to generate electricity. Taking the photovoltaic power generation system network as an example, the photovoltaic system may include a photovoltaic array, a junction box and an inverter. The photovoltaic array may be an array combination of multiple photovoltaic components. For example, multiple photovoltaic components can form multiple photovoltaic arrays. The photovoltaic array is connected to the junction box. The junction box can converge the current generated by the photovoltaic array. The converged current flows through the inverter and is converted into the alternating current required by the mains power grid, and then connected to the mains network to realize solar power supply.

[0087] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0088] Example 1

[0089] In this embodiment, a solar cell is prepared according to the following method:

[0090] 1. Ultrasonic clean the ITO glass with isopropanol, acetone, deionized water, and ethanol for 20 minutes in sequence, dry it, and then treat it with plasma for 180 seconds;

[0091] 2. Commercialization of NiO x The nanoparticles were dissolved in a mixed solvent of isopropyl alcohol (IPA) and water (IPA: H2O = 1:3) with a concentration of 0.04 M. The nanoparticles were deposited on the surface of the ITO glass substrate using a spin coating method in air at a spin coating speed of 3000 rpm and annealed at 150°C for 30 minutes to complete the NiO x Preparation, NiO x The thickness is 30nm.

[0092] 3. Dissolve MeO-2PACZ in 2-mercaptoethanol (2-ME) for later use.

[0093] 4.1.2M Perovskite (Cs 0.05 MA 0.1 FA 0.85 PbI 2.85 Br 0.15) Preparation of precursor solution: Dissolve a certain amount of FAI, MABr, CsI, PbBr2, and PbI2 in a DMF:NMP (6:1) mixed solvent and stir thoroughly to dissolve. Then, use a pipette to take the solution prepared in step 3 and add it to the perovskite precursor solution and mix thoroughly. The concentration of MeO-2PACZ is 0.5 mg / mL.

[0094] 5. The perovskite precursor solution containing MeO-2PACZ additive is deposited on the ITO / NiO obtained in step 2 by blade coating. x On the substrate, the tip height is 200 μm and the tip speed is 25 mm / s.

[0095] 6. After the coating is completed, the sample is transferred to a vacuum chamber for vacuum-assisted crystallization, with a vacuum degree of 100 Pa, a vacuuming time of 2 min, and a vacuuming rate of 8 L / s. The obtained perovskite film is annealed at 150 ° C for 10 min. The thickness of the prepared perovskite light-absorbing layer is 600 nm, and the additive content is 0.6‰.

[0096] 7. Transfer the perovskite sample to the vacuum coating chamber and deposit 30nm thick C by thermal evaporation. 60 as an electron transport layer and 5 nm thick BCP as an interfacial barrier layer.

[0097] 8. Deposit 80nm of silver electrode by vacuum thermal evaporation to complete the entire device preparation.

[0098] Example 2

[0099] In this embodiment, a solar cell is prepared according to the following method:

[0100] 1. Same as step 1 of Example 1;

[0101] 2. Dissolve nickel acetylacetonate in a mixed solvent of ethanol and diethanolamine (volume ratio 1:20-50) with a concentration of 0.02M, place it on a 70°C hot plate and stir for 12 hours, then add 20 times acetonitrile for dilution, and place it in a syringe pump for ultrasonic atomization spraying after dilution. Ultrasonic atomization spraying process: ultrasonic atomization power is 100%; injection speed is 1ml / min; nozzle to substrate distance is 40cm; airflow pressure is 260MPa; spray three times. Place the sprayed ITO glass on a 250°C heating table for annealing for 0.5h to complete the in-situ ultrasonic spraying of NiO x Preparation, NiO x Thickness: 30nm;

[0102] 3. Dissolve MPA-CPA in 2-mercaptoethanol (2-ME) for later use.

[0103] 4.1.2M Perovskite (Cs0.05 MA 0.1 FA 0.85 PbI 2.85 Br 0.15 ) Preparation of precursor solution: Dissolve a certain mass of FAI, MABr, CsI, PbBr2, and PbI2 in a DMF:NMP (6:1) mixed solvent and stir thoroughly to dissolve. Then, use a pipette to take the solution prepared in step 3 and add it to the perovskite precursor solution and mix thoroughly. The concentration of MPA-CPA is 3 mg / mL.

[0104] 5. The perovskite precursor solution containing MPA-CPA additives was deposited on the ITO / NiOx substrate obtained in step 2 by blade coating, with a blade height of 200 μm and a blade speed of 25 mm / s.

[0105] 6. After the coating is completed, the sample is transferred to a vacuum chamber for vacuum-assisted crystallization, with a vacuum degree of 100 Pa, a vacuuming time of 2 min, and a vacuuming rate of 8 L / s. The obtained perovskite film is annealed at 150 ° C for 10 min, and the thickness of the prepared perovskite light-absorbing layer is 600 nm, and the additive content is 3.6‰.

[0106] 7. Transfer the perovskite sample to the vacuum coating chamber and deposit 30nm thick C by thermal evaporation. 60 as an electron transport layer and 5 nm thick BCP as an interfacial barrier layer.

[0107] 8. Deposit 80nm of silver electrode by vacuum thermal evaporation to complete the entire device preparation.

[0108] Example 3

[0109] In this embodiment, a solar cell is prepared according to the following method:

[0110] 1. Ultrasonic clean the ITO glass with isopropanol, acetone, deionized water, and ethanol for 20 minutes in sequence, dry it, and then treat it with plasma for 180 seconds;

[0111] 2. NiO x It is deposited on the ITO surface by magnetron sputtering process. The sputtering process is as follows: in pure Ar gas atmosphere, the coating pressure is 0.8pa, and the sputtering power is 300W for 25 cycles to complete the NiOx preparation. The NiOx thickness is 30nm.

[0112] 3. Dissolve DMACPA in 2-mercaptoethanol (2-ME) for later use.

[0113] 4.1.2M Perovskite (Cs 0.05 MA 0.1 FA 0.85 PbI 2.85Br 0.15 ) Preparation of precursor solution: Dissolve a certain mass of FAI, MABr, CsI, PbBr2, and PbI2 in a DMF:NMP (6:1) mixed solvent and stir thoroughly to dissolve. Then, use a pipette to take the solution prepared in step 3 and add it to the perovskite precursor solution and mix thoroughly. The DMACPA concentration is 6 mg / mL.

[0114] 5. The perovskite precursor solution containing DMACPA additive is deposited on the ITO / NiO obtained in step 2 by blade coating. x On the substrate, the tip height is 200 μm and the tip speed is 25 mm / s.

[0115] 6. After the coating is completed, the sample is transferred to a vacuum chamber for vacuum-assisted crystallization, with a vacuum degree of 100 Pa, a vacuuming time of 2 min, and a vacuuming rate of 8 L / s. The obtained perovskite film is annealed at 150 ° C for 10 min, and the thickness of the prepared perovskite light-absorbing layer is 600 nm, and the additive content is 7.2‰.

[0116] 7. Transfer the perovskite sample to the vacuum coating chamber and deposit 30nm thick C by thermal evaporation. 60 as an electron transport layer and 5 nm thick BCP as an interfacial barrier layer.

[0117] 8. Deposit 80nm of silver electrode by vacuum thermal evaporation to complete the entire device preparation.

[0118] Example 4

[0119] In this embodiment, a solar cell is prepared according to the following method:

[0120] 1. Divide the 100mm×100mm ITO glass substrate into 12 sub-regions of equal area by laser scribing (P1 scribing, dividing the ITO region), each sub-region is 6mm wide. After cutting, the ITO glass is ultrasonically cleaned with isopropanol, acetone, deionized water, and ethanol for 20 minutes in sequence, and then dried and treated with plasma for 180s.

[0121] 2. Preparation of NiO by magnetron sputtering x The hole transport layer process is the same as that in Example 3.

[0122] 3-6. Same as steps 3-6 of Example 1.

[0123] 7. Transfer the perovskite sample to the vacuum coating chamber and deposit 30nm thick C by thermal evaporation. 60As the electron transport layer and 5nm thick BCP as the interface barrier layer. The sample after the electron transport layer and the interface barrier layer were evaporated was subjected to P2 scribing (P2 scribing removed the perovskite in a specific area and exposed the bottom ITO).

[0124] 8. Deposit 80nm silver electrode by vacuum thermal evaporation, and cut and connect 12 sub-cells in series by laser scribing P3 (scribing the silver electrode).

[0125] Example 5

[0126] In this embodiment, a solar cell is prepared according to the following method:

[0127] 1. Ultrasonic clean the ITO glass with isopropanol, acetone, deionized water, and ethanol for 20 minutes in sequence, dry it, and then treat it with plasma for 180 seconds;

[0128] 2. Commercialization of NiO x The nanoparticles were dissolved in a mixed solvent of isopropyl alcohol (IPA) and water (IPA: H2O = 1:3) and deposited on the surface of the ITO glass substrate by spin coating in air at a speed of 3000 rpm and annealed at 150°C for 30 minutes to complete the NiO x preparation.

[0129] 3. Dissolve MeO-2PACZ in 2-mercaptoethanol (2-ME) for later use.

[0130] 4.1.2M Perovskite (Cs 0.05 MA 0.1 FA 0.85 PbI 2.85 Br 0.15 ) Preparation of precursor solution: Dissolve a certain mass of FAI, MABr, CsI, PbBr2, and PbI2 in a DMF:NMP (6:1) mixed solvent and stir thoroughly to dissolve. Then, use a pipette to take the solution prepared in step 3 and add it to the perovskite precursor solution and mix thoroughly. The concentration of MeO-2PACZ is 15 mg / mL.

[0131] 5. The perovskite precursor solution containing MeO-2PACZ additive is deposited on the ITO / NiO obtained in step 2 by blade coating. x On the substrate, the tip height is 200 μm and the tip speed is 25 mm / s.

[0132] 6. After the coating is completed, the sample is transferred to a vacuum chamber for vacuum-assisted crystallization, with a vacuum degree of 100 Pa, a vacuuming time of 2 min, and a vacuuming rate of 8 L / s. The obtained perovskite film is annealed at 150 ° C for 10 min to obtain a perovskite light-absorbing layer with an additive content of 20‰.

[0133] 7. Transfer the perovskite sample to the vacuum coating chamber and deposit 30nm thick C by thermal evaporation. 60 as an electron transport layer and 5 nm thick BCP as an interfacial barrier layer.

[0134] 8. Deposit 80nm of silver electrode by vacuum thermal evaporation to complete the entire device preparation.

[0135] Comparative Example 1

[0136] The difference from Example 1 is that step 3 is not included, and step 4 is as follows:

[0137] 1.2M perovskite (Cs 0.05 MA 0.1 FA 0.85 PbI 2.85 Br 0.15 ) Preparation of precursor solution: Dissolve a certain mass of FAI, MABr, CsI, PbBr2, and PbI2 in a mixed solvent of DMF:NMP (6:1) and stir thoroughly to dissolve.

[0138] Comparative Example 2

[0139] The difference from Example 2 is that step 3 is not included, and step 4 is as follows:

[0140] 1.2M perovskite (Cs 0.05 MA 0.1 FA 0.85 PbI 2.85 Br 0.15 ) Preparation of precursor solution: Dissolve a certain mass of FAI, MABr, CsI, PbBr2, and PbI2 in a mixed solvent of DMF:NMP (6:1) and stir thoroughly to dissolve.

[0141] Comparative Example 3

[0142] The difference from Example 3 is that step 3 is not included, and step 4 is as follows:

[0143] 1.2M perovskite (Cs 0.05 MA 0.1 FA 0.85 PbI 2.85 Br 0.15 ) Preparation of precursor solution: Dissolve a certain mass of FAI, MABr, CsI, PbBr2, and PbI2 in a mixed solvent of DMF:NMP (6:1) and stir thoroughly to dissolve.

[0144] Comparative Example 4

[0145] In this comparative example, a solar cell was prepared according to the following method:

[0146] 1. Divide the 100mm×100mm ITO glass substrate into 12 sub-regions of equal area by laser scribing (P1 scribing, dividing the ITO region), each sub-region is 6mm wide. After cutting, the ITO glass is ultrasonically cleaned with isopropanol, acetone, deionized water, and ethanol for 20 minutes in sequence, and then dried and treated with plasma for 180s.

[0147] 2. The process of preparing the NiOx hole transport layer by magnetron sputtering is the same as that in Example 3.

[0148] 3. Disperse and dissolve MeO-2PACz in isopropanol solution and deposit it on magnetron sputtered NiO by blade coating. x The blade height was 200 μm and the scraping speed was 25 mm / s. Annealing was performed at 110°C for 10 minutes.

[0149] 4.1.2M Perovskite (Cs 0.05 MA 0.1 FA 0.85 PbI 2.85 Br 0.15 ) Preparation of precursor solution: Dissolve a certain mass of FAI, MABr, CsI, PbBr2, and PbI2 in a mixed solvent of DMF:NMP (6:1) and stir thoroughly to dissolve.

[0150] 5. The perovskite precursor solution was deposited on the MeO-2PACz / NiO obtained in step 3 by doctor blading. x / ITO substrate, the tool head height is 200μm and the tool head speed is 25mm / s.

[0151] 6. After the coating is completed, the sample is transferred to a vacuum chamber for vacuum-assisted crystallization, with a vacuum degree of 100 Pa, a vacuuming time of 2 min, and a vacuuming rate of 8 L / s. The obtained perovskite film is annealed at 150 ° C for 10 min. The thickness of the prepared perovskite light-absorbing layer is 600 nm, and the additive content is 0.5 mg / ml.

[0152] 7. Transfer the perovskite sample to the vacuum coating chamber and deposit 30nm thick C by thermal evaporation. 60 As the electron transport layer and 5nm thick BCP as the interface barrier layer. The sample after evaporation of the transport layer and the interface barrier layer was subjected to P2 scribing (P2 scribing removed the perovskite in a specific area and exposed the bottom ITO).

[0153] 8. Deposit 80nm silver electrode by vacuum thermal evaporation, and cut and connect 12 sub-cells in series by laser scribing P3 (scribing the silver electrode).

[0154] Test Case

[0155] The performance tests were performed on the solar cells prepared in the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 4 respectively.

[0156] The specific test method is: place the prepared battery device under a light source with an intensity P of 100mW / cm 2 AM1.5G standard simulates sunlight, and changes the bias voltage on the battery device to obtain the current value of the battery device, thereby drawing the current (Curent)-voltage (V) curve of the battery component, and thus obtaining the open circuit voltage Voc, short circuit current Curent, fill factor FF, and photoelectric conversion efficiency of the battery device, that is, battery efficiency PCE: the size of the component glass is 100*100mm 2 , divided into 12 sub-cell areas, with an effective area of ​​56cm 2 The V and J of the battery device change with the change of the external load. When the external load is short-circuited, V = 0, and the current at this time is called the short-circuit current; when the external load is disconnected, the current is 0, and V at this time is called the open circuit voltage Voc; the output power of the battery device has a maximum value, which is called the maximum power point Pmax. Pmax is divided by the effective light-receiving area of ​​the battery device, that is, the photoelectric conversion efficiency PCE; the fill factor FF of the battery device is P max / (Curent×Voc). Current=current density×Area.

[0157] The results are shown in Table 1. It can be seen that the performance of the solar cells prepared in Examples 1 to 5 is better than that in Comparative Examples 1 to 4.

[0158] Compared with Comparative Examples 1 to 3, the short-circuit current density, fill factor, open-circuit voltage and photoelectric conversion efficiency of the batteries prepared in Examples 1 to 3 are significantly improved. It can be seen that when SAMs are introduced into the perovskite solution, they are attached to the NiO from top to bottom during the crystallization process. x The nickel oxide surface contact can be efficiently passivated on the layer, thus constructing a good transport layer / perovskite contact interface and realizing the preparation of high-efficiency devices and components.

[0159] It can be seen from Example 4 and Comparative Example 4 that in Comparative Example 4, NiO x A SAMs passivation layer is formed on the surface, and then the perovskite precursor solution is deposited, resulting in poor wettability and holes ( Figure 3 a), while in Example 4, a perovskite precursor solution containing SAMs is deposited on the NiOx surface, and the wettability is good. The prepared perovskite film is relatively uniform and no holes appear ( Figure 3 b).

[0160] It can be seen from Examples 1 to 4 that different types of SAMs small molecules have good passivation effects on nickel oxide hole transport layers deposited by different methods when added to perovskite solutions, and the prepared component efficiencies are all around 20%, and the same small molecules also show good component efficiencies on different nickel oxide substrates. This result shows that the method of passivating the nickel oxide hole transport layer by adding SAMs small molecules to the perovskite precursor solution has a universal effect, and the magnitude of the improvement may be related to the nickel oxide process and the type of small molecules.

[0161] It can be seen from Examples 1 and 5 that when the concentration of Meo-2PACZ in the perovskite precursor solution is too high, the improvement of the passivation method is limited. SAMs do not participate in the perovskite crystallization process. When their concentration in the precursor solution is too high, it will affect the crystal quality in the perovskite film, resulting in a decrease in component performance.

[0162] Table 1 Performance parameters of solar cells obtained by different preparation methods

[0163]

[0164]

[0165] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A perovskite precursor solution, characterized in that: include: Perovskite precursors and self-assembled monolayer materials.

2. The perovskite precursor solution according to claim 1, characterized in that The self-assembled monolayer material includes at least one of MeO-2PACz, MPA-CPA, DMACPA, 2PACz, Me-4PACz, Br-4PACz, Br-2PACz, TBT-FBA, 4PADCB, and 2PADCB; And / or, the structural formula of the perovskite precursor is ABX3, wherein A includes at least one of methylamine ion, formamidine ion, acetamidine ion, cesium ion and rubidium ion; B includes at least one of lead ion, tin ion, copper ion and germanium ion; X includes at least one of fluoride ion, chloride ion, bromide ion, iodide ion, cyanide ion and thiocyanate ion.

3. The perovskite precursor solution according to claim 1 or 2, characterized in that: The concentration of the self-assembled monolayer material is 0.1 mg / mL to 10 mg / mL.

4. A solar cell, characterized in that: It comprises a perovskite light absorbing layer, wherein the perovskite light absorbing layer is formed by at least the perovskite precursor solution according to any one of claims 1 to 3.

5. The solar cell according to claim 4, characterized in that: A hole transport layer, a transparent conductive layer and a substrate are sequentially stacked on one side of the perovskite light absorbing layer, and an electron transport layer is stacked on the side of the perovskite light absorbing layer away from the hole transport layer.

6. The solar cell according to claim 5, characterized in that The hole transport layer includes NiO x .

7. The solar cell according to claim 5, characterized in that: An electrode layer is stacked on a side of the electron transport layer away from the perovskite light absorbing layer.

8. The solar cell according to claim 5, characterized in that: An interface barrier layer is stacked between the electron transport layer and the electrode layer, and the interface barrier layer includes at least one of TiO2, ZnO, SnO2, and BCP.

9. The solar cell according to claim 5, characterized in that: In the perovskite light absorbing layer, the concentration of the self-assembled monolayer material on the side close to the hole transport layer is higher than the concentration of the self-assembled monolayer material on the side away from the hole transport layer.

10. The solar cell according to claim 4 or 9, characterized in that: The self-assembled monolayer material accounts for 0.5‰ to 8‰ of the mass of the perovskite light-absorbing layer.

11. A method for preparing the solar cell according to any one of claims 5 to 10, characterized in that: include: forming the hole transport layer on a side of the transparent conductive layer stacked on one side of the substrate and away from the substrate; Applying the perovskite precursor solution according to any one of claims 1 to 3 on the side of the hole transport layer away from the transparent conductive layer, and annealing to form the perovskite light absorbing layer; The electron transport layer is formed on a side of the perovskite light absorbing layer away from the hole transport layer.

12. The method according to claim 11, characterized in that After applying the perovskite precursor solution to the side of the hole transport layer away from the transparent conductive layer, vacuum assisted crystallization is performed, and then the annealing is performed.

13. The method according to claim 12, characterized in that The vacuum assisted crystallization satisfies at least one of the following conditions: Vacuum degree: 10Pa~0.1MPa; 10pa-0.2Mpa Vacuum time is 1min~20min; The vacuum rate is 0.1L / s~10L / s.

14. The method according to claim 11, characterized in that The method of forming the hole transport layer comprises at least one of spin coating, solution deposition and magnetron sputtering; and / or, the method of applying the perovskite precursor solution comprises at least one of doctor blading, slit coating, spray coating and evaporation; And / or, the annealing temperature is 140° C. to 160° C., and the annealing time is 5 min to 20 min.

15. A photovoltaic module, characterized in that: The invention comprises: at least one battery string, wherein the battery string comprises at least two solar cells according to any one of claims 4 to 10.

16. A photovoltaic system, characterized in that: include: The photovoltaic module according to claim 15.